Haiti - Harmed at the Hands of Others - Max Ray-Ellis (Caribbean Studies Students' Union, 2023)
On January 1, 1804, Haiti officially proclaimed its Declaration of Independence, roughly two months after its forces led by Jean-Jacques Dessalines expelled the last remaining French forces from their territory. Their revolution had begun in 1791, when enslaved people sought to break free of brutal French colonial rule that originated in the mid-seventeenth century. The subsequent Haitian Constitution, published in 1805, detailed a "free and form sovereign state, independent of all the other powers of the universe," known as the "Haitian Empire," where "slavery is abolished forever" and "equality before the law is irrefutably established." The future appeared bright for this newly independent Black nation in the Caribbean. Unfortunately, for Haiti and the Haitian people, this bright future was not to be. For the past two plus centuries, Haiti has been continuously disadvantaged and subjected to mistreatment by other nations, including France and the United States. The potential for Haiti to emerge as a prosperous nation has thus been quashed due to numerous cases of foreign interference, which are still ongoing today.